NOVELLA SUÁREZ, Jorge (2021). La aventura del pensamiento español. Madrid: Sindéresis - Oscar Barroso Fernández (Daimon)
Reseña de NOVELLA SUÁREZ, Jorge (2021). La aventura del pensamiento español. Madrid: Sindéresis